ANALISIS SISTEM PENCAHAYAAN PADA GEDUNG FAKULTAS PERTANIAN UNIVERSITAS PATTIMURA AMBON - Siti Nursani Rumfot; Christy Gery Buyang; Fauzan Sangadji (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
This study aims to analyze the artificial lighting system in the building to determine whether the resulting illumination levels comply with the standards set by SNI 6197:2020. The main issue addressed is the low lighting which affects visual comfort and user productivity. This research adopts a descriptive quantitative method with observational and simulation approaches. Primary data were obtained through direct measurements using a lux meter and by collecting room dimension data, while secondary data were sourced from national standards and related journals. Lighting simulations were conducted using Dialux Evo software to visualize and evaluate lighting performance in each room. The results show that most rooms have lighting intensity levels below the standard. For instance, classrooms that should have 350 lux only recorded a maximum of 120 lux. The simulations carried out aim to visualize lighting more accurately. This study contributes significantly to the evaluation of lighting systems to be more effective and efficient